Integrative Research on Organic Matter Cycling Across Aquatic Gradients - Patricia M. Medeiros (Frontiers Research Topics, 2017)
The goal of this research topic was to motivate innovative research that blurs traditional disciplinary and geographical boundaries. As the scientific community continues to gain momentum and knowledge about how the natural world functions, it is increasingly important that we recognize the interconnected nature of earth systems and embrace the complexities of ecosystem transitions. We are pleased to present this body of work, which embodies the spirit of research spanning across the terrestrial-aquatic continuum, from mountains to the sea. Sincerely, The Editors